2019
DOI: 10.1187/cbe.19-01-0028
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Psychosocial Mechanisms Underlying STEM Persistence in Undergraduates: Scalability and Longitudinal Analysis of Three Cohorts from a Six-Day Pre–College Engagement STEM Academy Program

Abstract: In a previous report, we validated that a cohort of first-year undergraduates who participated in a weeklong pre–college engagement STEM Academy (SA) program were retained in science, technology, engineering, and mathematics (STEM) at a higher rate than a matched comparison group (MCG). In addition, SA students yielded increases in science identity and sense of belonging to STEM and to the university. Here, we report the ability to scale the size of the SA program to accommodate more students and replicate the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 41 publications
0
22
0
Order By: Relevance
“…In retrospect, Study 2's data are consistent with past STEM intervention research indicating that URG students do not consistently show changes in cognitive, motivational, and attitudinal changes throughout college (Dennehy and Dasgupta, 2017;Estrada et al, 2019). First, students who enter college in pursuit of STEM typically demonstrate high STEM self-efficacy, but often experience a decrease in selfefficacy when they are exposed to the rigors of STEM coursework and expectations (Liu, 2018;Kuchynka et al, 2019). It appears that self-efficacy drops are explained in part by the anxiety and self-doubt experienced during the transition from high school to college (Rosenthal et al, 2011), and the stress experienced when transferring from a 2-years to 4-years institutions (Laanan, 2001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In retrospect, Study 2's data are consistent with past STEM intervention research indicating that URG students do not consistently show changes in cognitive, motivational, and attitudinal changes throughout college (Dennehy and Dasgupta, 2017;Estrada et al, 2019). First, students who enter college in pursuit of STEM typically demonstrate high STEM self-efficacy, but often experience a decrease in selfefficacy when they are exposed to the rigors of STEM coursework and expectations (Liu, 2018;Kuchynka et al, 2019). It appears that self-efficacy drops are explained in part by the anxiety and self-doubt experienced during the transition from high school to college (Rosenthal et al, 2011), and the stress experienced when transferring from a 2-years to 4-years institutions (Laanan, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Instead of exclusively focusing on how to increase self-efficacy and future intentions, researchers should also address research questions about how to protect these psychological constructs during critical periods of development. Past research highlights the instability of self-efficacy during transition periods and college (Estrada et al, 2019;Kuchynka et al, 2019;Liu, 2018;Rosenthal et al, 2011). The community college students participating in Study 2's mentorship program sought to transfer to a 4-year university, and started the intervention with relatively strong intentions to pursue STEM and high self-efficacy levels.…”
Section: Community Collegementioning
confidence: 99%
“…SDT states that the more a person's psychological needs are met, the more internally motivated they will be in that particular situation (27). Research on different aspects of biology education has shown that SDT can explain the positive effects of teambased learning (28), socio scientific issues-based laboratory curricula (29), mentoring interventions (30), and STEM retention resulting from scalable STEM academy programs (31,32).…”
Section: Sdt and Fostering Student Successmentioning
confidence: 99%
“…Many K‐12 teachers across the United States have classroom sizes with over 25 students (Taie & Goldring, 2020) making it difficult to implement educational recommendations such as cultivating relational classrooms with active learning components. Applying lessons learned from college STEM outreach programs, teachers and school districts should focus on small‐group interactions to create cooperative and collaborative STEM environments that foster meaningful relationships (Kuchynka et al., 2019). That is, one way to address these high student‐teacher ratios is to develop small‐group interactions with about six students per group (Kuchynka et al., 2019).…”
Section: Stem Education and Policy Recommendationsmentioning
confidence: 99%